2004
DOI: 10.1038/sj.npp.1300520
|View full text |Cite
|
Sign up to set email alerts
|

1H MRS Study of Dorsolateral Prefrontal Cortex in Healthy Individuals before and after Lithium Administration

Abstract: The mechanism of action of lithium is still largely unknown. However, recent animal and human studies suggested the possible neuroprotective effects of this medication. In particular, a recent magnetic resonance spectroscopy (MRS) study showed the increase of cortical brain levels of N-acetyl-aspartate (NAA), a putative marker of neuronal integrity/functioning, in both bipolar patients and normal controls after 4 weeks of lithium administration. We investigated the effects of lithium on NAA levels in a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 38 publications
1
35
1
1
Order By: Relevance
“…The difference in our study vs the Chang study is that the increase in our cohort was only identified in those subjects with low levels at baseline. The baseline NAA by remit status interaction is as well consistent with the hypothesis originally proposed by Brambilla et al, (2004) whereby treatment-associated increases in NAA may only be identified in NAA deficient disease states. In their study, lithium administration to healthy controls was not associated with an increase in NAA.…”
Section: Discussionsupporting
confidence: 89%
“…The difference in our study vs the Chang study is that the increase in our cohort was only identified in those subjects with low levels at baseline. The baseline NAA by remit status interaction is as well consistent with the hypothesis originally proposed by Brambilla et al, (2004) whereby treatment-associated increases in NAA may only be identified in NAA deficient disease states. In their study, lithium administration to healthy controls was not associated with an increase in NAA.…”
Section: Discussionsupporting
confidence: 89%
“…10 However, a recent clinical study on control subjects taking chronic lithium showed no changes in NAA. 77 It remains unclear whether the NAA increase after lithium treatment is a diseasespecific effect, or an effect on baseline brain chemistry. In our study, neither chronic lithium nor chronic valproate treatment increased NAA levels in the rat brain.…”
Section: Post-mortem Brain Tissue Analysismentioning
confidence: 99%
“…[8][9][10][11][12][13] Smaller hippocampal volumes are among the most replicated neuroimaging findings in patients with major depressive disorder compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%